2016
DOI: 10.14814/phy2.13014
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids increase skeletal muscle NFκB inducing kinase (NIK): links to muscle atrophy

Abstract: Glucocorticoids (GC) are a frontline therapy for numerous acute and chronic diseases because of their demonstrated efficacy at reducing systemic inflammation. An unintended side effect of GC therapy is the stimulation of skeletal muscle atrophy. Pathophysiological mechanisms responsible for GC‐induced skeletal muscle atrophy have been extensively investigated, and the ability to treat patients with GC without unintended muscle atrophy has yet to be realized. We have reported that a single, standard‐of‐care dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“… 54 It was also reported that methylprednisolone is able to increase the NFκB-inducing kinase expression in human skeletal muscle. 55 Further studies are required for the new IT-inducing pharmacological therapy for patients with PDA.…”
Section: Discussionmentioning
confidence: 99%
“… 54 It was also reported that methylprednisolone is able to increase the NFκB-inducing kinase expression in human skeletal muscle. 55 Further studies are required for the new IT-inducing pharmacological therapy for patients with PDA.…”
Section: Discussionmentioning
confidence: 99%
“…), and NFкB (Fry et al . ). Hence, due to continual basal stress, aged muscle is unable to further upregulate crucial stress responsive proteins, demonstrating a marked loss in age‐dependent adaptability when challenged with an acute exercise bout (Vasilaki et al .…”
Section: Introductionmentioning
confidence: 97%
“…Upstream regulation of NF-κB activation was reported to occur in skeletal muscle atrophy via increasing in vivo expression of NF-κB inducing kinase following glucocorticoid administration [25]. Early and intermediate stage supraspinatus tendon disease increased expression of genes and proteins regulated by NF-κB activation pathways [26].…”
Section: Discussionmentioning
confidence: 99%